The History of the Heretics in Jarh Wa Ta'dil: Relevance to Hadith Validity - Musadad, Endad; Arifin, Azis (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
The importance of the dimension 'is' is so significant that Ajaz al-Khatib asserts that the status of weak hadith cannot ascend to the level of Hasan, even if supported by various chains of transmission (Shawahid and Tawawbi’), when the personal integrity of the narrator in the chain of transmission is questioned by hadith critics. This writing aims to examine the status of the narrations of bid’ah within the scholarly realm of Jarh wa Ta'dil. This research employs a qualitative approach using library research methods and the science of hadith. The findings of this study indicate that hadith scholars assess that, to some extent, bid’ah in Jarh wa Ta'dil can still be tolerated as long as it is not extreme or considered a major of bid’ah, including bid’ah that do not render the perpetrator as a disbeliever. The rejection of narrations from innovators is fundamentally not a discriminatory act but rather a demonstration of sincerity and caution against the possible fabrication of hadith by irresponsible individuals.